Perspektif Mahasiswa Terhadap Judi Online di Indonesia: Wujud Kesadaran Hukum dan Etika Digital Warga Negara - Hanum, Fathikah Fauziah; Fathurrahman, Ali Masykur; Kusdarini, Eny; Febiantoni, Fungki; Aziz, Sulthon Abdul (Jurnal Kewarganegaraan, 2025)
This study analyzes students' perspectives on online gambling regulations in Indonesia. It focuses on understanding students who are part of the younger generation and actively engage in the digital world to assess legal awareness and digital ethics among citizens. The research employs a quantitative descriptive method using a cross-sectional approach and was conducted at a university in Yogyakarta. Stratified random sampling was used for sample selection, and data were collected through a questionnaire, which served as a non-test instrument. The data analysis technique utilized was quantitative data analysis. The results indicated that students' knowledge and understanding of online gambling regulations fell into the "very good" category. Their attitudes and views regarding the economic impact of online gambling were similarly classified as "very good." Personal experience in this area showed a "good" category rating, indicating the students' high legal awareness and digital ethics level. However, a significant number of students expressed that educational institutions do not provide sufficient information or support concerning issues surrounding online gambling. Citizenship Education plays a crucial role in addressing this issue, along with campus regulations for prevention and intervention.